Flamingo foraging activity as a driver of spatial heterogeneity in Langebaan Lagoon, South Africa - Payne, Robyn (Department of Biological Sciences, 2014)
Numerous studies have attempted to quantify the effect of epifaunal predation and its co-occurring disturbance on macrofaunal communities with the aid of exclosure experiments. However, no attention has been paid to the possible impacts of different foraging methods used by flamingos on benthic communities. Multivariate and univariate analyses were carried out in order to determine the effects of two different flamingo feeding strategies (pit and channel foraging) on sediment penetrability and macrofaunal community structure in Langebaan Lagoon. The two foraging strategies appear only to differ with regards to prey removal and recolonisation. The more energy intensive, pitforming foraging enables the flamingo to obtain higher quantities of Urothoe grimaldii in addition to bivalves, while promoting recolonisation by opportunists. On the other hand, channel-foraging enables the attainment of various polychaete and nematode species. These small-scale differences, as well as the spatial (and possibly temporal) variation in structures generate habitat complexity. Thus, this preliminary study supports the notion that flamingo foraging activity is a key driver of spatial heterogeneity in Langebaan Lagoon and highlights the need for further research.